Development and Validation of PubMed and Ovid MEDLINE Search Filters for Exposure Pathways Linking Climate Change With Public Health - Maria‐Inti Metzendorf; Ina Monsef; Katherine Jones; L Susan Wieland; Heidrun Janka; Camila Escobar Liquitay; Denise Thomson (Cochrane Evidence Synthesis and Methods, 2026)
ABSTRACT Introduction Climate change has major health impacts to which researchers and policymakers need to respond. The volume and multidisciplinary nature of climate‐health evidence pose challenges to its comprehensive identification. Search filters are currently not available for this topic. Our aim was to empirically develop sensitivity‐maximizing climate‐health search filters for two interfaces of the MEDLINE database. Methods Climate change impacts health via several exposure pathways involving distinct mechanisms: extreme weather events, heat stress, air quality, water quality and quantity, food supply and safety, vector distribution and ecology, and social factors. Using the relative recall method, we established a gold standard by extracting included studies of 110 evidence syntheses and classifying them into exposure pathways. From this set, we empirically derived and validated filters per pathway. Results Based on 1572 primary studies indexed in PubMed, we developed filters with a sensitivity of 95%, 97% and 99% for six of the seven major climate‐health exposure pathways. Conclusion We designed the first empirically derived search filters for climate‐health pathways, enabling sensitive retrieval despite acknowledged limitations. Our filters can be applied to different types of research questions at the intersection of climate and health.